The sum of the interior angles, s, in an n-sided polygon can be determined using the formula s=180(n−2), where n is the number of sides.
Using this formula, how many sides does a polygon have if the sum of the interior angles is 1,260°? Round to the nearest whole number.

Answers

Answer 1

Answer:

The polygon has 9 sides

Step-by-step explanation:

We need to equate the given expression to the given value and solve for n.

The sum of the interior angles, s, in an n-sided polygon is given by the expression:

[tex]s = 180(n - 2)[/tex]

We want to use this formula, to calculate how many sides has a polygon if the sum of the interior angles is 1,260°.

We solve the following equation for n.

[tex]180(n - 2) = 1260[/tex]

Divide through by 180 to get:

[tex] \frac{180(n - 2)}{180} = \frac{1260}{180} [/tex]

[tex]n - 2 = 7[/tex]

Add 2 to both sides to get:

[tex]n = 7 + 2[/tex]

[tex] \therefore \: n = 9[/tex]

Hence the polygon has 9 sides

Answer 2

Answer: d

Step-by-step explanation:


Related Questions

Suppose the odds in favor of me being nice are given as 100:1. What is the probability that the next time we meet I will be nice?

Answers

the probabiltity is:

outcome/total possible outcomes

therefore, 100/101

The probability that the next time we meet I will be nice is [tex]\frac{100}{101}[/tex].

Given that,

Suppose the odds in favor of me being nice are given as 100:1.

Based on the above information, the calculation is as follows:

[tex]= 100 \div (100 + 1)\\\\= 100\div 101[/tex]

Therefore we can conclude that The probability that the next time we meet I will be nice is [tex]\frac{100}{101}[/tex].

Learn more: brainly.com/question/17429689

Which linear inequality is graphed with y>-x-2 to create the given solution set?

Answers

Answer

D

Step-by-step explanation:

just toke the test

Two equations are given below:

a − 3b = 16
a = b − 2

What is the solution to the set of equations in the form (a, b)?
(−2, −6)
(−7, −9)
(−11, −9)
(−12, −10)

Answers

Answer:

(-11,-9)

Step-by-step explanation:

b-2-3b=16

-2b-2=16

-2b=18

b= -9

a= -9-2

a=-11

If f(x) is a third degree polynomial function how many distinc complex rules are possible ?

Answers

Answer:

2

Step-by-step explanation:

According to the fundamental theorem of Algebra

A polynomial of degree 3 has 3 roots

However, complex roots occur in conjugate pairs, hence

There can only be 2 distinct complex roots.

SOLVE y = 3x – 2 x – y = 4 BY USING SUBSTITUTION!! SHOW ALL WORK! HELPPP!

Answers

Answer:

(-1,-5)

Step-by-step explanation:

So we have the system:

y=3x-2

x-y=4.

We are asked to use substitution. Luckily, it is already setup for this because one of the equations has one of the variables solved for, namely the y=3x-2 equation.  We are going to insert y=3x-2 into x-y=4 and solve for x.

x-y=4  (with y=(3x-2) ):

x-(3x-2)=4

Distribute:

x-3x+2=4

Combine like terms:

-2x+2=4

Subtract 2 on both sides:

-2x    =2

Divide both sides by -2:

 x     =-1

Now if y=3x-2 and x=-1, then y=3(-1)-2=-3-2=-5.

So the solution is (-1,-5).

Solve the equation for the indicated variable
A = 8v for v

Answers

Answer:

A=8v

8v=A

8v/8=A/8

v=A/8 answer

Help me with this question

Answers

Answer: Base.

The exponent is the 2, and the 5 is the base.

Answer:

Step-by-step explanation:

The five is the base. The two tells you what to do with the base.

5^2 = 5 * 5 = 25.

Notice what you are told. The 2 tells you to use two fives. The ^ in this case means multiply.

What is 12% of 4? Explain and Show your work

Answers

Answer:

0.48

Step-by-step explanation:

convert the percent to a decimal

12%=0.12

multiply 4 by 0.12

you're left with 0.48

you can check your math by dividing .48/.12, which will give you 4

To solve this you must use a proportion like so...

[tex]\frac{part}{whole} = \frac{part}{whole}[/tex]

12 is a percent and percent's are always taken out of the 100. This means that one proportion will have 12 as the part and 100 as the whole

We want to know what is 12% of the number 4. This means 4 is the whole and the unknown (let's make this x) is the part.

[tex]\frac{x}{4} =\frac{12}{100}[/tex]

Now you must cross multiply

x*100 = 4*12

100x = 48

Now isolate x divide 100 to both sides

100x/100 = 48/100

0.48 = x

This means that 12% of 4is 0.48

Hope this helped!

~Just a girl in love with Shawn Mendes

PLEASE HELP!!! ASAP!!!!!!

Answers

6 units right is the answer, since plugging in values(since it's asking for the translation you can ignore the -3) so your answer is:

The graph is translated 6 units RIGHT

Hope this helps!

plz brainliest

Select the values that are solutions to the inequality x2 + 3x – 4 > 0.

Answers

The solutions to the inequality x^2 + 3x - 4 > 0 are all real numbers where x is less than -4 or greater than 1, represented by the intervals (x < -4) or (x > 1).

To find the values that are solutions to the inequality x2 + 3x - 4 > 0, we first need to determine the roots of the quadratic equation x2 + 3x - 4 = 0. We can do this either by factoring, completing the square, or using the quadratic formula. In this case, factoring is the simplest approach:

x2 + 4x - x - 4 = 0

(x + 4)(x - 1) = 0

Therefore, the roots are x = -4 and x = 1. Since it is a parabola opening upwards (the coefficient of x2 being positive), the inequality x2 + 3x - 4 > 0 holds true when x is either less than -4 or greater than 1.

The solution set is thus all real numbers outside the interval [-4, 1], which can be written as (x < -4) or (x > 1).

which of the following is the probability that a Blue Marble will not be selected from a bag containing 9 red marbles 6 blue marbles 7 green Marbles and 11 yellow marbles if one is selected randomly

79%
32%
18%
82%​

Answers

Answer: 82%

Step-by-step explanation: Count the total number of marbles.

9+6+7+11=33 marbles in total.

We are trying to find the probability of NOT picking a blue marble. There are 6 blue marbles. Subtract the blue marbles from the total.

33-6=27

The probability of not picking a blue marble is 27/33. Divide the fraction.

27/33=0.82

Multiply by 100 to get the percent.

0.82 x 100 = 82%

There is an 82% chance of not picking a blue marble.

Ifa-b=4 and a^2- b^2=3, what is the value of a+b?

Answers

Answer:

[tex]\large\boxed{a+b=\dfrac{3}{4}}[/tex]

Step-by-step explanation:

[tex]\text{Use}\ a^2-b^2=(a-b)(a+b).\\\\\text{We have}\ a-b=4\ \text{and}\ a^2-b^2=3.\\\\\text{Substitute:}\\\\3=4(a+b)\qquad\text{divide both sides by 4}\\\\\dfrac{3}{4}=(a+b)\to a+b=\dfrac{3}{4}[/tex]

10 - 4(2.4 • 3.5)2 + 0.12 10 - 4(8.4)2 + 0.12 10 - 4(70.56) + 0.12

Answers

Answer:

- 406.278

Step-by-step explanation:

10 - 4(2.4 • 3.5)2 + 0.12 10 - 4(8.4)2 + 0.12 10 - 4(70.56) + 0.12

Using BODMAS rule, first operation under bracket will be done. Then after Multiplication, addition and subtraction will be solved.

= 10 - 4 (8.4) 2 + 0.1210 - 4(8.4) 2 + 0.1210 - 4 (70.56) + 0.12

= 10 - 67.2 + 0.1210 - 67.2 + 0.1210 - 282.24 + 0.12

= - 406.278

Choose a system of equations with the same solution as the following system: 6x + 2y = −6 3x − 4y = −18

Answers

Final answer:

To find a system with the same solution, multiply one of the original equations by a constant and/or add the two original equations together to derive a new equation. An example is the alternative system 6x - 8y = -36 and 9x - 2y = -24, which shares the same solution as the original.

Explanation:

To find a system of equations with the same solution as the given system:

6x + 2y = −6

3x − 4y = −18

We must ensure that the alternative system is equivalent, meaning they share the same solution. A common technique is to multiply both sides of one or both of the equations by a constant to create new equations that have the same solutions. For example, we could multiply the second equation by 2:

3x − 4y = −18 becomes 6x − 8y = −36 after multiplying by 2.

Then, to avoid having the same equation, we could add the original second equation to the first one to get a different second equation:

6x + 2y + (3x − 4y) = −6 + (−18) becomes 9x − 2y = −24.

So, the alternate system that shares the same solution as the original would be:

6x − 8y = −36

9x − 2y = −24

How many different 5-letter words can be created using the letters M, A, G, I, C without any letter being used more than once?

Answers

Answer:

You can spell only one word using the letters (M,A,G,I,C) the only word able to be made would be magic.

Step-by-step explanation:

Hope this helped you! :3

Answer:Meets,Abuzz,Glows,Inner,Creepy

Step-by-step explanation:

Which of the following is the radical expression of a^4/9

Answers

For this case we must find an expression equivalent to:

[tex]a ^ {\frac {4} {9}}[/tex]

By definition of properties of powers and roots we have:

[tex]\sqrt [n] {a ^ m} = a ^ {\frac {m} {n}}[/tex]

So, rewriting the expression we have:

[tex]\sqrt [9] {a ^ 4}[/tex]

Answer:

Option 4

Answer: OPTION 4.

Step-by-step explanation:

By definition, Radical expressions are those that use a root.

In this case you have this expression:

[tex]a^{\frac{4}{9}[/tex]

 In order to find the radical expression of  [tex]a^{\frac{4}{9}[/tex], it is important to remember that:

[tex]a^\frac{m}{n}=\sqrt[n]{a^m}[/tex]

Therefore, once you apply this, you get:

 [tex]a^{\frac{4}{9}=\sqrt[9]{a^4}[/tex]

You can observe that it matches with the expression provided in Option 4.

Explain how System 1 becomes equivalent to System 2.
System 1:
AX + By = C
LX + My=N
System 2:
(A + L)X + (8 + M)y = C+N
AX + By = C

A.The first equation in System 2 is the sum of the equations in System 1. The second equation in System 2 is the first equation in System 1.

B.The first equation in System 2 is the difference of the equations in System 1. The second equation in System 2 is the first equation in System 1.

C.The first equation in System 1 is the sum of the equations in System 2. The second equation in System 1 is the second equation in System 2.

D.The first equation in System 1 is the difference of the equations in System 2. The second equation in System 1 is the second equation in System 2.​

Answers

Answer:

[tex]\left\{\begin{array}{ccc}(A+L)x+(B+M)y=C+N\\Ax+By=C\end{array}\right[/tex]

A.The first equation in System 2 is the sum of the equations in System 1. The second equation in System 2 is the first equation in System 1.

Step-by-step explanation:

[tex]\underline{+\left\{\begin{array}{ccc}Ax+By=C\\Lx+My=N\end{array}\right}\qquad\text{add both sides of the equations}\\(Ax+Lx)+(By+My)=C+N\qquad\text{distributive}\\(A+L)x+(B+M)y=C+N[/tex]

Equivalent expressions are expressions that have the same value.

The true statement is: (a) The first equation in System 2 is the sum of the equations in System 1. The second equation in System 2 is the first equation in System 1.

The systems of equations are:

System 1

[tex]\mathbf{Ax + By = C}[/tex]

[tex]\mathbf{Lx + My = N}[/tex]

System 2

[tex]\mathbf{(A + L)x + (8 + M)y = C + N}[/tex]

[tex]\mathbf{Ax + By = C}[/tex]

When the equations of system 1 are added, we have:

[tex]\mathbf{Ax + Lx + By + My = C + D}[/tex]

Factor out x and y

[tex]\mathbf{(A + L)x + (8 + M)y = C + N}[/tex]

The above equation is the first equation of system 2.

While [tex]\mathbf{Ax + By = C}[/tex] is the second equation of the system

Hence, the true statement is (a)

Read more about systems of equations at:

https://brainly.com/question/13997560

Here are the heights in inches of 10 professional basketball players: 66, 74, 76, 77, 78, 79, 80, 80, 82, 84. The mean of these heights is 77.6 inches. Does this set have an outlier and, if so, how does removing it affect the mean?


The set has 66 as an outlier and removing it decreases the mean by about 1.3 inches.


The set has 66 as an outlier and removing it increases the mean by about 1.3 inches.


The set has 66 as an outlier and removing it decreases the mean by about 6.6 inches.


The set has no outliers.




Question 5
Here are 10 test scores: 50, 74, 76, 77, 78, 79, 80, 80, 82, 84. The mean of these scores is 76. How does removing the outlier 50 affect the mean?


The set has 50 as an outlier and removing it decreases the mean by about 10.


The set has 50 as an outlier and removing it decreases the mean by about 2.


The set has 50 as an outlier and removing it increases the mean by about 3.


The set has 50 as an outlier and removing it decreases the mean by about 6.

Answers

Answer:

Question 4: The set has 66 as an outlier and removing it increases the mean by about 1.3 inches.

Question 5: The set has 50 as an outlier and removing it increases the mean by about 3.

Step-by-step explanation:

Question 4:

Given heights are:

66, 74, 76, 77, 78, 79, 80, 80, 82, 84

The mean is: 77.6 inches

Removing 66 will make the mean increase to 78.9

So,

The set has 66 as an outlier and removing it increases the mean by about 1.3 inches.

Question 5:

50, 74, 76, 77, 78, 79, 80, 80, 82, 84

The mean is 76.

We can clearly see that 50 is an outlier as it is quite less than the given data.

Calculating mean after removing 50 will give us mean equal to 78.9

So the correct answer is:

The set has 50 as an outlier and removing it increases the mean by about 3.

3 (x - 1) = 3x - ________

What would 3x be subtracted by

Answers

Answer:

3

Step-by-step explanation:

Answer: 3

Step-by-step explanation:

Use the distributive property:

  3(x - 1)

= 3(x) + 3(-1)

= 3x  - 3

         

Use the given area to find XY. A. 8 cm B. 12 cm C. 16 cm D. 24 cm

Answers

Answer:

A

Step-by-step explanation:

Since the triangles are similar then the ratio of corresponding sides = a : b

and ratio of areas = a² : b²

Here the ratio of areas = 7 : 28 = 1 : 4, hence

ratio of sides = [tex]\sqrt{1}[/tex] : [tex]\sqrt{4}[/tex] = 1 : 2

Hence

XY = 2 × DE = 2 × 4 = 8 cm

The answer is XY=2*DE=2*4=8cm, in summary, eight cenimeters.

Simplify to create an equivalent expression. −y−3(−3y+5)

Answers

Answer:

[tex]\large\boxed{-y-3(-3y+5)=8y-15}[/tex]

Step-by-step explanation:

[tex]-y-3(-3y+5)\qquad\text{use the distributive porerty}\ a(b+c)=ab+ac\\\\=-y+(-3)(-3y)+(-3)(5)\\\\=-y+9y-15\qquad\text{combine like terms}\\\\=(-y+9y)-15\\\\=8y-15[/tex]

the simplified expression is 8y−15

To simplify the expression −y−3(−3y+5), we can start by distributing the negative sign to each term inside the parentheses.

This gives us −y+9y−15. Next, we can combine like terms by adding the coefficients of the y-terms, which gives us 8y.

Finally, we combine the constant terms to get −15.

Therefore, the simplified expression is 8y−15. We simplified the original expression by distributing the negative sign and then combining like terms to obtain a more concise and equivalent expression.

Learn more about expression here

https://brainly.com/question/28316105

#SPJ6

Thirty cities were researched to determine whether they had a professional sports team, a symphony, or a children's museum of these cities, 15 had a professional
sports team 15 had a symphony, 13 had a children's museum, 8 had a professional sports team and a symphony, 7 had a professional sports team and a children's
museum 7 had a symphony and a children's museum, and 3 had all three activities Complete parts a) through e) below​

Answers

Answer:

the way its set up its kind of confusing

Step-by-step explanation:

Answer:

Step-by-step explanation:

cities were researched to determine whether they had a professional sports​ team, a​ symphony, or a​ children's museum. Of these​ cities,  had a professional sports​ team,  had a​ symphony,  had a​ children's museum,  had a professional sports team and a​ symphony,  had a professional sports team and a​ children's museum,  had a symphony and a​ children's museum, and  had all three activities. Complete parts ​a) through ​e) below.

Evaluate sin-1(-1/2) for the angles between 0 and 360°
PLEASE HELP!!!!

Answers

Check the picture below, notice the angles encircled in purple.

Which of the following is the inverse of f(x)=-2x+3

Answers

The inverse of [tex]\( f(x) = -2x + 3 \)[/tex] is [tex]\[ f^{-1}(x) = \frac{x - 3}{-2} \][/tex].

To find the inverse of f(x) = -2x + 3 , you need to interchange  x  and  y and solve for y .

Start with y = -2x + 3 .

Swap x  and y  to get  x = -2y + 3 .

Solve this equation for  y .

x = -2y + 3

First, subtract 3 from both sides:

x - 3 = -2y

Then, divide both sides by -2 :

[tex]\[ \frac{x - 3}{-2} = y \][/tex]

Thus, the inverse of [tex]\( f(x) = -2x + 3 \)[/tex] is:

[tex]\[ f^{-1}(x) = \frac{x - 3}{-2} \][/tex]

help!! asap!
A bucket of paint has spilled on a tile floor. The paint flow can be expressed with the function p(t) = 5t, where t represents time in minutes and p represents how far the paint is spreading.

The flowing paint is creating a circular pattern on the tile. The area of the pattern can be expressed as A(p) = πp2.

Part A: Find the area of the circle of spilled paint as a function of time, or A[p(t)]. Show your work. (6 points)

Part B: How large is the area of spilled paint after 2 minutes? You may use 3.14 to approximate π in this problem. (4 points)

Answers

Answer:

A) A(p(t)) = 25πt²

B) 314 square units.

Step-by-step explanation:

Part A)

Flow of paint can be expressed by the function:

p(t) = 5t

Area of the pattern is expressed as:

A(p) = πp²

Since area is given in terms of p, we can use the expression of p to express the area of pattern in terms of time(t). Using the value, we get:

A(p(t)) = π (5t)²

A(p(t)) = 25πt²

Part B)

We have to calculate the area of the pattern after time t. Substituting the value of t in above expression, we get:

A(p(2)) = 25 x 3.14 x 4 = 314 square units.

Therefore, the area of spilled paint after 2 minutes will be 314 square units.

a train traveling at an average speed of 85 miles per hour. At this rate, how far will the train travel in 12 1/4 hours?

Answers

Answer:

1041.25 miles

Step-by-step explanation:

You just have to multiply 12.25 (which is equivalent to 12 1/4) by 85 and you'll get the answer 1041.25

Answer:

1041.248 miles

Step-by-step explanation:

Points to remember

Speed = Distance/Time

It is given that,a train traveling at an average speed of 85 miles per hour.

To find the speed of train

Speed = 85 miles/1

 = 136.794 km/1 = 136.794 km/hr

To find the distance traveled in 12 1/4 hours

Distance = Speed * time

 = 136.794 * 12 1/4

 = 136.794 * 49/4

 = 1675.7265

 = 1041.248 miles

Given EG = 16 and FH = 12, what is the length of one side
of the rhombus?

6 units
8 units
10 units
14 units

Answers

Answer: 10 units

Step-by-step explanation:

The length of one side of the given rhombus is; C: 10 units

What is the length of the rhombus?

The half diagonals of a rhombus are the legs of a right angle triangle with the hypotenuse being the side of the rhombus.

We see that EG and FH are the diagonals of the rhombus. This means that the half-diagonals measure 8 and 6.

Using Pythagoras theorem, we can find the hypotenuse which is the length of the side of the rhombus.

Thus;

8² + 6² = c²

64 + 36 = c²

100 = c²

c² = 100

c = 10

In conclusion, the length of one side of the rhombus is 10 units

Read more about length of rhombus at; https://brainly.com/question/26154016

Is BES - GES? If so, identify the similarity postulate or theorem that
applies​

Answers

Answer:

A

Step-by-step explanation:

∠BES = ∠GES = 40°

∠BSE = ∠GSE = 90°

ΔBES and ΔGES are similar by the AA postulate → A

The given ΔBES and ΔGES are similar triangles according to the AA similarity postulate or theorem. Option A true.

What is the AA similarity postulate or theorem?

The AA similarity postulate is that " If any two triangles have a pair of angles with equal measures then they are said to be similar triangles". If two angles are equal then the third one will also be equal in both the triangles.

Checking similarity in both the triangles:

The given triangles are ΔBES and ΔGES

The ΔBES has dimensions as ∠BES=40° and ∠ESB=90° and the ΔGES has dimensions as ∠GES=40° and ∠ESG=90°

Thus, both the triangles have pair of angles with equal measures. I.e., ∠BES=∠GES=40° and ∠ESB=∠ESG=90°. So, they satisfy the AA similarity theorem.

Hence, the given triangles are said to be similar according to the AA similarity postulate or theorem. So, option A is true.

Learn more about similarity postulates here:

https://brainly.com/question/21247688

#SPJ2

the width of the credit card is 5.6 CM what is in millimeters​

Answers

Answer: 56

Step-by-step explanation:

For this case we must make a conversion of centimeters to millimeters. By definition we have to:

1 cm equals 10 mm

By making a rule of three we have:

1 cm ---------> 10 mm

5.6 cm --------> x

Where "x" represents the quantity in millimeters.

[tex]x = \frac {5.6 * 10} {1} = 56[/tex]

Thus, we have that 5.6 centimeters equals 56 millimeters.

Answer:

56mm

What is the solution to the equation fraction 1 over 6 x = 2?

x = fraction 1 over 12

x = fraction 1 over 3

x = 3

x = 12

Answers

C=1/12
1/6x=2 so 1=12x
X=1/12

Answer:

C=1/12

1/6x=2 so 1=12x

X=1/12

Step-by-step explanation:

Other Questions
Excess supply is created when price or move away from the equilibrium point. true or false Which of the following points lie in the solution set to the following system of inequalities?[tex]y < - 3x + 3 \\ y < x + 2[/tex]A.(1,-5)B.(1,5)C.(5,1)D.(-1,5) A boxcar traveling at 8 m/s approaches a string of 4 identical boxcars sitting stationary on the track. The moving boxcar collides and links with the stationary cars and they all move off together along the track. What is the final speed of the cars immediately after the colision? (You may take the mass of each boxcar to be 18,537 kg.) What does the equipotentiality hypothesis suggest would happen if the hippocampus was damaged? a.another part of the brain would compensate for the damage by taking over the memory function normally managed by the hippocampus b.areas near the hippocampus would decay, followed by a cascading failure of the brain leading to death c.people would lose their ability to feel fear d.people would become comatose Consider how you respond to major events in your life. When something significant happens, how do you typically respond? Check all that apply. -call your friends - write in a journal - get more talkative -become quiet and reserved- compare your situation to others - focus on your unique experience Y=8x-11Y=x-17Solve the system of equations Write an exponential function y = abx for a graph that includes (1, 15) and (0, 6). Which statement accurately describes the virgins plan Which of the following is the solution of 5e2x - 4 = 11? A. X=In 3B.In 27 C. X=In13/2D.X=3/In3 I need help ASAP please Your order is supposed to be delivered between 5PM-6PM, and its now 5:45PM. Youre stuck in a long line waiting to check out. In this situation, you will be late delivering the order. Provide an example of the text message you would send to the member. Fill in the blank with the correct form of "to be" in the present tense: Ellesde Belgique.O A. sontO B. estO C. tesO D. sommes QUESTIONS The average price of wheat per metric ton in 2012 was $30575. Demand in millions of metric tons) in 2012 was 672. The average price of wheat per metric ton in 2013 was $291.56, while the demand was 700. Calculate the elasticity and classify as elastic or inelastic -0.04 elastic -0.9, elastic -0.9; inelastic -3.84, elastic -0.04 inelastic graph the equation by translating y=|x|y=|X+2| A celling fan has two different angular speed setting: omega_1 = 440 rev/min and omega_2 = 110 rev/min. what is the ratio a_1/a_2 of the centripetal accelerations of a given point on a blade? The wavelength of the red-pink line emitted by a laboratory sample of excited hydrogen is 656 nm. Taking a spectrum of a glowing nebula, you find that the same red-pink line of hydrogen appears at 662 nm. You conclude that the nebulaA. Is 1% hotter than hydrogen in the laboratory sample.B. Is moving towards us at about 1% the speed of light.C. Is 1% cooler than hydrogen in the laboratory sample.D. Is moving away from us at about 1% the speed of light What is a Trojan?(I'm talking about the computer virus) Help!!!!!!!!!!!!!!!!!!!!!!!!! What is the measure of angle C? The standard reduction potentials of lithium metal and chlorine gas are as follows: Reaction Reduction potential (V) Li+(aq)+eLi(s) 3.04 Cl2(g)+2e2Cl(aq) +1.36 In a galvanic cell, the two half-reactions combine to 2Li(s)+Cl2(g)2Li+(aq)+2Cl(aq) Calculate the cell potential of this reaction under standard reaction conditions.